Prebiotic potential of natural gums and starch for bifidobacteria of variable origins. (October 2019) - Modrackova, Nikol; Makovska, Marie; Mekadim, Chahrazed; Vlkova, Eva; Tejnecky, Vaclav; Bolechova, Petra; Bunesova, Vera
Abstract: Complex polysaccharide polymers of natural origin are widely used as natural food thickeners. They are useful for their technological properties, and at the same time they are biodegradable and safe for consumers. In addition, natural food thickeners, such as natural gums (NGs) and starch, may also represent suitable potentially prebiotic substrates for probiotic genera such as the genus Bifidobacterium . Therefore, 204 bifidobacterial strains of 60 species and subspecies were tested for their ability to utilize 6 NGs (locust bean, guar, tragacanth, arabic, xanthan, and karaya gums) and starch. Here we observed that the ability to utilize these substrates as a single carbon source is species and strain specific trait reflecting the host origin and diet. The utilization was evaluated based on the pH change, metabolite formation, and detection of viable bifidobacterial counts. In conclusion, 114 strains of human and animal origin (37 bifidobacterial species and subspecies) were able to utilize starch. Compared to that, mostly bifidobacteria of the animal origin were able to utilize a wider range of available natural substrates compared to the human bifidobacteria. In total, 29 strains were able to use NGs (10 species and subspecies). Most often used locust bean, guar, tragacanth, and arabic gums represent possible prebiotic sources for bifidobacteria in animal nutrition, ideally in synbiotic applications. Natural food thickeners were found to be useful potential prebiotics. However, a suitable combination with probiotic Bifidobacterium strains is required. Graphical abstract: Image 1 Highlights: Natural food thickeners (NFT) are technologically useful, biodegradable and safe. Locust bean, guar, and arabic gums are possible bifidogenic prebiotic sources. Animal bifidobacteria utilize wider range of NFTs compared to human. Utilization ability of bifidobacteria is host, species and strain specific.